Analysis of The Queue System in Self-Service Using The "ABC Supermarket" Queue Method - Islami, Mega Cattleya P.A; Winursito, Yekti Condro; Saputro, Erwan Adi; Noviani, Siti Alya (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2024)
A queuing system is a mathematical model used to analyze the phenomenon where entities wait to receive services from one or more service providers. In this system, arriving entities will queue if the service is not immediately available and will be served according to a specific order or priority when the service becomes available. ABC Supermarket is a store that is always busy with customers. Besides having low prices, ABC Supermarket also provides daily necessities. The purpose of this research is to determine whether the cashier queue system implemented at ABC Supermarket is effective or not. This research uses the queue system method. This research concludes that the queue system at ABC Supermarket with 6 cashiers has an average ρ value percentage of 41.67%, which falls into the ineffective category. The most effective number of cashiers is 3, with an average r value percentage of 83.33%, which falls into the effective category. The purpose of queuing system analysis is to optimize the performance of the queuing process by determining the optimal number of service providers required.